Crop Yields and Soil Phosphorus Lability under Soluble and Humic‐Complexed Phosphate Fertilizers. (1st July 2016) - Bejarano Herrera, Wilfrand Ferney; Rodrigues, Marcos; Bettoni Teles, Ana Paula; Barth, Gabriel; Pavinato, Paulo Sergio
Abstract : Phosphorus is one of the most limiting nutrients for plants in weathered tropical soils. To overcome this constraint, the use of humic‐complexed phosphate fertilizer may be considered as one alternative, which would reduce P fixation and increase its bioavailability. This study aimed to determine the crop yield response and soil P lability changes after five crop cycles under humic‐complexed and non‐humic‐complexed superphosphate cumulative applications. The field experiment was conducted for 4 yr (2010–2013) in Tibagi, Brazil, in a Typic Hapludox, arranged in a randomized block design with two P sources; single superphosphate (SSP) and complexed single superphosphate (CSSP); and five cumulative dosages (0, 48, 96, 144, and 192 kg P ha −1 ), divided over five consecutive crops: maize ( Zea mays L.), wheat ( Triticum aestivum L.), soybean [ Glycine max (L.) Merr.], white oat ( Avena sativa L.), and soybean. Grain yield was determined for each crop and soil samples were collected after the fifth harvest for Hedley P fractionation. Our results demonstrated that cumulative grain yield increased in line with the P dosage, however, higher agronomic efficiency was also observed at intermediate P dosages, when CSSP was used. Labile soil P was more influenced by the application of CSSP than SSP. Moreover, higher cumulative P dosages also increased labile and non‐labile P, mainly in the 0‐ to 5‐cm layer, indicating an intensive P pool reallocation in the surface soil layer. The study demonstrated that humic‐complexed phosphate fertilizer can enhance soil P availability and improve crop grain yield in commercial field conditions. Core Ideas Phosphate fertilizers efficiency in cropping system. Residual effects of phosphate sources in tropical weathered soils. Organic complexed fertilizers can be more efficient in plant P supply. Soil labile P is affected by clay content and its adsorption capacity.